Integrasi Prinsip-Prinsip Manajemen dalam Pendidikan Sekolah Minggu - Oeei, Sheren (Tumou Tou, 2025)
This study aims to analyse the application of management principles in the implementation of non-formal education in church Sunday Schools. The results reveal that the effective and efficient learning process requires the application of management principles, including planning, organizing, implementation, and supervision. Careful planning, including the development of a structured curriculum, is key to achieving educational goals and improving students' understanding. Using a phenomenology research method, this study emphasizes that the application of management principles in Sunday Schools is of great importance in supporting the achievement of effective and efficient education, as well as ensuring the fulfilment of the Great Commission of Jesus Christ through Sunday School education